2019
DOI: 10.1590/1982-0224-20180004
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the structure of the ichthyoplankton community in the lower Paraíba do Sul River

Abstract: The Paraíba do Sul River is affected by extensive water collection for supply, organic and industrial pollution, and dams. Nonetheless, the ichthyofauna maintains biodiversity and sustains artisanal fisheries. This study analyzes the composition, abundance and distribution of fish larvae, an important approach to determine the reproductive period and spawning sites. The sampling occurred from August 2011 through February 2013 in five sites at a transect between the banks on the lower reach of the Paraíba do Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Limnological factors have a strong relationship and synchronism with organisms, especially fish. They directly influence reproduction, occurrence and distribution of eggs and larvae, an integration that has been demonstrated in several studies (Lopes & Zaniboni‐Filho, 2019; Teixeira et al., 2019; Zacardi, Ferreira, et al., 2017), indicating that these environmental mechanisms can provide better conditions for growth and survival (Ponte et al., 2019; Zacardi et al., 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Limnological factors have a strong relationship and synchronism with organisms, especially fish. They directly influence reproduction, occurrence and distribution of eggs and larvae, an integration that has been demonstrated in several studies (Lopes & Zaniboni‐Filho, 2019; Teixeira et al., 2019; Zacardi, Ferreira, et al., 2017), indicating that these environmental mechanisms can provide better conditions for growth and survival (Ponte et al., 2019; Zacardi et al., 2020).…”
Section: Discussionmentioning
confidence: 74%
“…The physical and chemical conditions of the waters (temperature, 30.00 ± 00°C; salinity, 32.11 ± 2.08 ‰; and pH, 6.78 ± 0.32) were optimal to support the spawning activity of striped eel catfish. In several other fish species, the spawning season is influenced by the aquatic environment and food availability, migration tactics, and age structure (Yoneda and Wright 2015;Gallagher et al 2018;Arula et al 2019;Teixeira et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The response of aquatic biota to water bodies depends on the physical and chemical characteristics of the water bodies and is expected to give different responses to the reproductive biology of striped eel catfish in Kolono Bay. Many studies have reported that differences in fish responses are related to water conditions at different locations (Barbosa et al 2018;Asriyana and Irawati 2019;Teixeira et al 2019). This study investigated reproductive traits and spawning activity of striped eel catfish, P. lineatus, in Kolono Bay.…”
Section: Introductionmentioning
confidence: 99%
“…The highest ichthyoplankton densities during the drought phase may have been strongly influenced by the occurrence of rainfall since, during November 2021 (drought phase), there was precipitation before the rainy season. As rainfall is considered a key environmental factor for the gene flow of species, it directly influences the abundance of fish eggs and larvae (Ferreira et al, 2016;Teixeira et al, 2019;Sanches et al, 2020;Badú et al, 2022). Furthermore, temporal variability of ichthyoplankton drift is related to functional characteristics and life history of each species (Nagel et al, 2021;Gogola et al, 2022).…”
Section: Figurementioning
confidence: 99%